2015
DOI: 10.15453/2168-6408.1142
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Confidence and Knowledge of Evidence-Based Practice among Occupational Therapy Students

Abstract: Evidence-based practice (EBP) is used throughout multiple health-care professions and includes the use of best research available, client preferences, and the practitioner's experience. Occupational therapy educational programs are required to incorporate EBP into their curriculum. A convenience sample of occupational therapy students from a private university completed a survey designed to measure students' knowledge and confidence in EBP. The survey consisted of the Knowledge of Research Evidence Competencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(69 reference statements)
3
19
0
Order By: Relevance
“…Future testing with experienced users of the BDM could identify if knowledge increases correspondingly with confidence levels. This would align with other findings of a correlation between confidence and knowledge increasing among occupational therapy students as evidence‐based practice experience increased (DeCleene Huber et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Future testing with experienced users of the BDM could identify if knowledge increases correspondingly with confidence levels. This would align with other findings of a correlation between confidence and knowledge increasing among occupational therapy students as evidence‐based practice experience increased (DeCleene Huber et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…2 Evidence-based practice (EBP) plays an integral role in high-quality healthcare by promoting a problemsolving approach that emphasises implementation of the current best available research within a clinical context, helping healthcare professionals to remain up-to-date and make better healthcare decisions. [3][4][5][6][7] The National Academy of Medicine in the USA recognises EBP as an essential skill for healthcare providers in the 21 st century. 8 Several studies have also indicated that EBP improves the quality and safety of patient care.…”
Section: Application To Patient Care -The Implementation Of Ebp Is a mentioning
confidence: 99%
“…8 Several studies have also indicated that EBP improves the quality and safety of patient care. 6,7,9 Nevertheless, many healthcare decisions are still based on traditional practices, assumptions, personal experiences and individual opinions and skills. 10,11 The possession of adequate knowledge and skills is essential for gathering and appraising evidence and implementing best practices in a clinical setting.…”
Section: Application To Patient Care -The Implementation Of Ebp Is a mentioning
confidence: 99%
“…Fieldwork education is instrumental in fostering the habits needed to become an evidence-based practitioner (DeCleene Huber et al, 2015;Stronge & Cahill, 2011;Stube & Jedlicka, 2007;Thomas & Law, 2013). Exposure to EBP during fieldwork fosters the students' confidence in their ability to use evidence in practice, which may, in turn, influence their use of EBP when they are clinicians (DeCleene Huber et al, 2015;Thomas & Law, 2013). However, students may have difficulty considering themselves as evidence-based practitioners if they do not perceive their fieldwork educator as an evidence-based practitioner (Stronge & Cahill, 2011).…”
mentioning
confidence: 99%
“…The multidimensional nature of EBP may prevent students from recognizing its application during fieldwork, which may, in turn, limit their ability to apply evidence in practice (DeCleene Huber et al, 2015). These findings are significant; however, the problem may be even more complex.…”
mentioning
confidence: 99%